2005
DOI: 10.1103/physrevb.72.104106
|View full text |Cite
|
Sign up to set email alerts
|

Two-step phase changes in cubic relaxor ferroelectrics

Abstract: Abstract:The field-driven conversion between the zero-field-cooled frozen relaxor state and a ferroelectric state of several cubic relaxors is found to occur in at least two distinct steps, after a period of creep, as a function of time. The relaxation of this state back to a relaxor state under warming in zero field also occurs via two or more sharp steps, in contrast to a one-step relaxation of the ferroelectric state formed by field-cooling. An intermediate state can be trapped by interrupting the polarizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
0
13
0
7
Order By: Relevance
“…This observation is in good agreement with the results obtained for polycrystalline BNT‐100 x BT samples doped with manganese, where a single‐peak depolarization current curve was observed for low BT‐content, but multiple peaks appeared as the composition entered the MPB region. A similar process has been observed by Colla and Weissmann in the temperature‐induced depolarization of rhombohedral 0.94(PbMg 1/3 Nb 2/3 O 3 )‐0.06PbTiO 3 (PMN‐6PT) . Their explanation is based on the relaxor character of the transition and the existence of different types of PNR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is in good agreement with the results obtained for polycrystalline BNT‐100 x BT samples doped with manganese, where a single‐peak depolarization current curve was observed for low BT‐content, but multiple peaks appeared as the composition entered the MPB region. A similar process has been observed by Colla and Weissmann in the temperature‐induced depolarization of rhombohedral 0.94(PbMg 1/3 Nb 2/3 O 3 )‐0.06PbTiO 3 (PMN‐6PT) . Their explanation is based on the relaxor character of the transition and the existence of different types of PNR.…”
Section: Discussionmentioning
confidence: 99%
“…4(c) and (f)]. This type of loop is again an indication for a multistep polarization reversal process, 44 but this time it does not involve the decay of long-range ordered ferroelectric domains into PNR. Two observations lead to this conclusion: first, polarization reversal via PNR was never observed more than 20°C below T F-R in previous studies.…”
Section: (1) Depolarization Behavior and Thermal Phase Stabilitymentioning
confidence: 91%
See 1 more Smart Citation
“…16,17 The most fascinating aspect of PMN lies in its nonergodic states under bias electric fields. [18][19][20][21][22][23][24][25][26][27][28][29] The polar nanoregions in PMN can grow into micrometer-sized ferroelectric domains when driven by external electric fields, which corresponds to a field-induced phase transition. 20,30,31 The transition kinetics study has shown that when a static field is applied to a zerofield-cooled crystal along the ͗111͘ direction, the phase transition takes place abruptly after an incubation period.…”
Section: Introductionmentioning
confidence: 99%
“…% Mn doped BN6BT 25 and high-strain relaxor (PbMg 1/3 Nb 2/3 O 3 ) 0.94 (PbTiO 3 ) 0.06 (Ref. 38) were attributed to different types of PNRs. The coexistence of tetragonal and rhombohedral PNRs, which respond differently to external field, is likely responsible for the irregular depolarization behavior.…”
Section: Resultsmentioning
confidence: 99%